Peran Guru dalam Mengembangkan Kreativitas Siswa pada Pelajaran Puisi dalam Kurikulum Deep Learning - Salwa Nadifah Mariyah; Daffa Firdaus (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
This study aims to analyze the role of teachers in developing students' creativity in poetry lessons in the Deep Learning curriculum. The curriculum emphasizes deep understanding and learning that focuses on the student experience. In this context, teachers play an important role as facilitators who not only teach poetry writing techniques, but also provide space for students to express their creative ideas. This study uses a qualitative approach by collecting data through observation, interviews, and documentation studies. The results of the study show that the role of teachers is very vital in creating a learning environment that supports students' creativity, both in providing inspiration, guidance, and creative freedom. In addition, teachers must also be able to recognize students' potential and encourage them to think critically and innovatively in creating poetry works.